2010
DOI: 10.1248/bpb.33.1828
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Induces Mitochondria Dependent Apoptosis in Prostate Cancer Cells in Association with an Inhibition of Phosphoinositide 3-Kinase/AKT Pathway

Abstract: Apoptosis, also called programmed cell death, is morphologically characterized by cell shrinkage, membrane remodeling, cell blebbing, chromatin condensation and DNA fragmentation with apoptotic bodies.1-3) Apoptosis activation has been considered a good target in cancer therapies. 4,5) In general, apoptosis is regulated by pro-apoptotic and antiapoptotic proteins of the Bcl-2 family and executed through caspases (or cysteine-aspartic proteases), chiefly via two major and inter-related pathways, i.e., the mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
64
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 38 publications
8
64
1
Order By: Relevance
“…The results presented here show that TSA inhibited ischemia-induced cell death in the entorhinal cortex. This finding parallels that of a study using prostatic cancer cells, where TSA also had an anti-apoptic effect (Won et al, 2010). Since many neurodegenerative diseases involve cell death and inappropriately elevated levels of immune activity, it is likely that an agent such as TSA with anti-inflammatory and anti-apoptic properties, will also find application in the treatment of a broader range of age-related diseases of the nervous system.…”
Section: Discussionsupporting
confidence: 77%
“…The results presented here show that TSA inhibited ischemia-induced cell death in the entorhinal cortex. This finding parallels that of a study using prostatic cancer cells, where TSA also had an anti-apoptic effect (Won et al, 2010). Since many neurodegenerative diseases involve cell death and inappropriately elevated levels of immune activity, it is likely that an agent such as TSA with anti-inflammatory and anti-apoptic properties, will also find application in the treatment of a broader range of age-related diseases of the nervous system.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, the anti-apoptotic mechanism of TCTP has also been associated with antagonization of Bax (21). Tan-IIA also downregulates expression of the mitochondrial protective Bcl-2 family memeber MCL-1, inducing apoptosis in prostate cancer cells (22). These observations indicate that Tan-IIA inhibits protein expression of TCTP, MCL-1 and Bcl-xl to destroy mitochondrial function and increase Bax and Caspase-3 expression, inducing apoptosis in human pancreatic …”
Section: A B Cmentioning
confidence: 92%
“…The cardiovascular pharmacological effects of TanIIA include preventing atherosclerosis, shortening the myocardial infarction area, reducing myocardial oxygen consumption, and inhibiting thrombosis formation and platelet aggregation (Xu et al, 2006). Data indicate that Tan has better clinical prospects as an anti-tumor drug, as previous studies have shown that TanIIA can induce apoptosis in cervical cancer cells, HL-60 cells, and K562 cells, although its mechanism of action requires further study (Sung et al, 1999;Wang et al, 2003;Shan et al, 2009;Won et al, 2010;Chiu and Su, 2010;Yun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%